"Would I Have Been Better Off There?" Comparison, Need, and Conduciveness in Finnish Emigrant’s Account - Ulrika Wolf-Knuts (Journal of Ethnology and Folkloristics)
Processes of comparison are central when we make our decisive choices of ways of living. This article is based on an interview with an immigrant who negotiates with himself over why he went away from Finland and why he stayed in South Africa. His line of argument can be analysed using Abraham Maslow’s theory of human motivation. Conduciveness turns out to be his main motivation, and comparison is, implicitly or explicitly, a tool for verbalising this conduciveness.